HOW INFLUENCERS AND ONLINE CUSTOMER REVIEWS SHAPE REPURCHASE INTENTION IN FAST-FOOD MSMES: THE MEDIATING ROLE OF CUSTOMER TRUST AND THE MODERATING ROLE OF PRODUCT INVOLVEMENT - Rizma Fauziyah; Agus Hermawan; Madziatul ChuriyMala (RADJA PUBLIKA, 2026)
Increasingly intense competition in the micro, small, and medium-sized food and beverage (MSME) sector requires businesses to understand the mechanisms that encourage customers to make repeat purchases. This study analyzes the influence of influencers and online customer reviews on repurchase intention, both directly and through customer trust, and examines the role of product involvement in moderating the relationship between influencers and repurchase intention. The research conceptual framework was developed based on Stimulus–Organism–Response Theory, which positions influencers and online customer reviews as stimuli, customer trust as an internal psychological state, and repurchase intention as a behavioral response. The study used a quantitative explanatory design with a cross-sectional approach. Data were collected through questionnaires from 210 customers of MSMEs in the fast food F&B sector in Malang City selected using purposive sampling. Analysis was conducted through partial least squares structural equation modeling using SmartPLS 4.0. The results showed that influencers and online customer reviews have a positive and significant effect on customer trust. Customer trust also has a positive effect on repurchase intention. Influencers did not have a significant direct influence on repurchase intention, while online customer reviews showed a positive influence with significance at the limit of statistical acceptance. Customer trust mediated the influence of influencers and online customer reviews on repurchase intention. Product involvement was not shown to moderate the relationship between influencers and repurchase intention. These findings suggest that the effectiveness of influencer communication in driving repeat purchases depends primarily on their ability to build trust in MSMEs. Customer reviews serve a dual function as a source of evaluative information and as a basis for forming consumer beliefs. Practical implications emphasize the importance of consistent product quality, communication